ANALISIS MODEL PEMBELAJARAN BERBASIS WEB (E-LEARNING) DALAM PEMBELAJARAN SEKOLAH DASAR. - Henny Setiani; Sri Nurfadilah; Siti Intan Hawa Safitri; Faridatul Bahiyah; Lailatul Mahfudoh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the implementation of web-based learning models (e-learning) in elementary schools and examine their effectiveness in improving student engagement and learning quality. The study was motivated by the increasing need for digital transformation in elementary education. This research employed a qualitative approach using a literature review method. Data sources consisted of national and international journal articles related to e-learning implementation in elementary schools published between 2020–2026. Data collection techniques were conducted through documentation and literature review, while data analysis involved data reduction, data presentation, and conclusion drawing. The findings indicate that web-based learning contributes positively to students’ learning engagement, independence, participation, and digital literacy skills. Interactive content and multimedia-based platforms provide more meaningful learning experiences. Therefore, web-based learning can serve as an effective alternative in supporting learning activities in elementary schools.